Sincronismo comportamental em Boto cinza(Sotalia guianensis) - Tosi, Caroline Herédia (2007)
Synchronism is the efetivation of the same behavior at the same time by two or more individuals. In cetology only from 2000 we verify an increasing of efforts for studies of synchronic behaviors. The synchronism in cetaceans was reported for a variety of contexts, including feeding, socializing, parental care, while resting, traveling and play, during afilliation, in sexual behaviour and possible while teaching. The synchronism in behavior is influenced by environmental factors and can be modified during stress situations such as the presence of boats. The aim of this study is to explore behavior synchronism presented by the estuarine dolphin (Sotalia guianensis) in Pipa, Rio Grande do Norte state, Northeastern Brazil. A total of 414 hours of observation during the year 2006, using scan sampling method, from a land based sighting was conducted. Analyses were conducted in four steps. Firstly, we determined the pattern of activity of the groups within the bay, testing for the influence of bay configuration before and after rains periods on the activity of animals. Analyses show that forage occurs more frequently after the rainy period, but there was no change in the number of individuals or spatial cohesions between them. Secondly, we analysed the influence of turism boat traffic on the behavior of animals. We verified no changes on the bahavior of animals during the presence of boats. Finally, we tested seven hypotheses regarding the ecological and social dynamics of synchronic behavior. Environmental aspects were considered the main influence for the synchronism, no influences of age, and more selective exihibition of synchronic breathing in feeding and social displays were observed during the study period